Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Akuntansi Untuk Berkarir Sebagai Akuntan Publik - Taufik Daniel Saputra Sabetiliake; Enny Arita (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2024)
This research aims to determine the influence of financial awards, professional recognition, work environment, and job market considerations on accounting students' interest in pursuing a career as a public accountant. The population in this study were Bachelor of Accounting students from the Class of 2020 and 2021. The results of this research indicate that financial awards, professional recognition, work environment and job market considerations have a positive influence on undergraduate accounting students' interest in pursuing a career as a public accountant